2016
DOI: 10.4314/stech.v5i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Review of Courtyard House in Nigeria: definitions, history, evolution, typology, and functions

Abstract: The courtyard is one among the familiar concepts commonly applied in the design of buildings in almost all the Nigerian cultural groups. It is truly the traditional expression of Nigerian indigenous architecture. Its definition, historical evolution, functions and typology is worth investigating. Also, its adaptation to the contemporary architectural design and practice in different building typology in the Nigerian context will be studied. Different courtyard house studies were examined through Journal papers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…The turning point in the morphology of indigenous architecture was the extroversion of the Yoruba buildings to face the street and the village court rather than the internal courtyard of the family compound (Markus, 2016;Jolaoso & Bello, 2019). The extroversion of the buildings arrived at the same time with the organisation of the urban setting along European styled streets.…”
Section: Figure 5 a Relic Of The Early Vernacular Stylementioning
confidence: 99%
“…The turning point in the morphology of indigenous architecture was the extroversion of the Yoruba buildings to face the street and the village court rather than the internal courtyard of the family compound (Markus, 2016;Jolaoso & Bello, 2019). The extroversion of the buildings arrived at the same time with the organisation of the urban setting along European styled streets.…”
Section: Figure 5 a Relic Of The Early Vernacular Stylementioning
confidence: 99%
“…Studies of existing courtyard configurations all across Nigeria identified a variety of compositions that could be categorized as vernacular, colonial, post-colonial and modern (Table 1). This concept of architecture is seen in various building types (Table 2), ranging from residential buildings to administrative, institutional, health, educational, and multi-functional buildings [22] .…”
Section: Courtyard Configurations In the Study Areamentioning
confidence: 99%
“…But, the social and functional benefits of the courtyard, for instance, seclusion and security, lighting and air circulation within the courtyard and the building, seems to be of greater significance than the problem of microclimate performance, as revealed by Markus (2016c), and other scholars such as Muhaisen and Gadi (2006a), Muhaisen and Gadi (2006b). They argued that the courtyard microclimatic performance should be more paramount than its social benefits.…”
Section: Theoretical Backgroundmentioning
confidence: 99%